PERLINDUNGAN HUKUM BAGI KORBAN PERDAGANGAN ORANG DI DAERAH JAWA BARAT (KAJIAN DI DAERAH BANDUNG, SUKABUMI, CIMAHI, INDRAMAYU, DAN GARUT) - Mety Rahmawati Argo (The Juris, 2018)
Trafficking in persons is a violation of human rights, which must be eradicated. His victims suffered greatly, both materially and non-material. Causes the victim to feel insecure, and is not guaranteed his rights. The State has an obligation to guarantee the fulfillment of the rights of victims of trafficking in persons. The purpose of this study is to obtain a description of the provision of legal protection to victims of trafficking in persons, using qualitative research methods, using the theory of preventive legal protection aimed at preventing the occurrence of disputes, directing government actions to be cautious in decision-making based on discretion, and repressive protection aims to resolve the dispute, including its handling at the judiciary. The results of this study indicate that the provision of legal protection to victims of trafficking in persons in the Regional Regulations of each study area, implemented after the condition and facilities owned infrastructure. Protection is provided, but not entirely, primarily for compensation, restitution, non-identity publication, still inconsistent.